Donor Finger Morbidity in Cross-Finger Flap: A Systematic Review and Meta-Analysis - Chakraborty, Sourabh Shankar; Sahu, Ranjit Kumar; Acharya, Sudeshna; Goel, Akhil Dhanesh; Midya, Manojit; Kotu, Suresh (Indian Journal of Plastic Surgery, 2023)
Background The morbidity of donor finger in a cross-finger flap has not received as much importance as the outcomes of the flap itself. The sensory, functional, and aesthetic morbidity of donor fingers, reported by various authors, are often contradictory to each other. In this study, objective parameters for the sensory recovery, stiffness, cold intolerance, cosmetic outcome, and other complications in the donor fingers, reported in the previous studies, are systematically evaluated.Methods This systematic review is reported using Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) protocol and was registered with the International prospective register of systematic reviews (PROSPERO registration no. CRD42020213721). Literature search was done using “cross-finger,” “heterodigital,” “donor finger,” and “transdigital” words. Data regarding demography, patients' number and age, follow-up duration and outcomes of donor finger, including 2-point discrimination, range of motion (ROM), cold intolerance, questionnaires, etc. were extracted from included studies. Meta-analysis was performed using MetaXL and risk of bias was evaluated using Cochrane risk of bias tool.Results Out of the total 16 included studies, 279 patients were objectively evaluated for donor finger morbidity. Middle finger was most frequently used as donor. Static two-point discrimination seemed to be impaired in donor finger in comparison to contralateral finger. Meta-analysis of ROM suggested that statistically there is no significant difference in ROM of interphalangeal joints in donor and control fingers (pooled weighted mean difference: −12.10; 95% confidence interval: −28.59, 4.39; I2 = 81%, n = 6 studies). One-third of donor fingers had cold intolerance.Conclusion There is no significant effect on ROM of donor finger. However, the impairment that seems to be in sensory recovery and aesthetic outcomes needs to be further evaluated objectively.
Keywords: cross-finger flap; donor finger; morbidity; systematic review